2012
DOI: 10.1038/tp.2012.33
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic gene polymorphisms and response to psychological therapy

Abstract: Therapygenetics, the study of genetic determinants of response to psychological therapies, is in its infancy. Here, we investigate whether single-nucleotide polymorphisms in nerve growth factor (NGF) (rs6330) and brain-derived neutrotrophic factor (BDNF) (rs6265) genes predict the response to cognitive behaviour therapy (CBT). Neurotrophic genes represent plausible candidate genes: they are implicated in synaptic plasticity, response to stress, and are widely expressed in brain areas involved in mood and cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 79 publications
(94 reference statements)
0
42
2
Order By: Relevance
“…In this study, we find genotype‐dependent changes in methylation during treatment are associated with treatment outcomes at follow‐up . Previous studies investigating both genetic26, 30, 32 and epigenetic26, 27 markers of response to psychological therapy have also demonstrated the largest effects at follow‐up. Future research of predictors and markers of response to psychological therapies would be improved by including this time point.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, we find genotype‐dependent changes in methylation during treatment are associated with treatment outcomes at follow‐up . Previous studies investigating both genetic26, 30, 32 and epigenetic26, 27 markers of response to psychological therapy have also demonstrated the largest effects at follow‐up. Future research of predictors and markers of response to psychological therapies would be improved by including this time point.…”
Section: Discussionmentioning
confidence: 97%
“…In a recent study, anxiety disordered children carrying two copies of the "s" allele of the serotonin transporter promoter polymorphism (5HTTLPR) were 20 % more likely to be disorder free at follow-up after CBT than l/l or s/l carriers [39]. The same group found a polymorphism in the gene for nerve growth factor (NGF) to be relevant for psychotherapy treatment outcomes in children suffering from anxiety disorder [74]. However, these findings await replication.…”
Section: Implications Of Genetic Findings For Prevention and Therapeumentioning
confidence: 99%
“…A study on male hamsters has shown that differential action of BDNF caused dominant- Single nucleotide polymorphic variants of BDNF (rs6265, Val66Met) and NGF (rs6330, Ala35Val) have been reported to be associated with anxiety phenotypes in humans (58).…”
Section: Role Of Ngfs In Maintenance Of Normal Behaviourmentioning
confidence: 99%